The Gender Gap among Teen Survey Respondents: Why are Boys more Likely to Report a Gun in the Home than Girls? - Cook, Philip J. (2005)
It is a reliable though unexplained feature of national surveys that include items on gun ownership that wives are less likely to report a gun in the home than husbands. In this article we extend the inquiry regarding this gender gap in reporting of household guns to include adolescent children (age 12–17 years). The California Health Interview Survey of 2001, the largest-ever state survey of its kind, includes over 4000 marital households in which both a parent and adolescent child were interviewed and asked whether there was a gun in the home. There is little age gap in reporting - California teens are almost as likely to say that there is a gun as are their parents - but there is a gender gap among both the teens and their parents. We also find a large gap in personal experience with guns - boys are three times as likely to report hunting or shooting with a family member than girls. This difference in experience fully accounts for the gender gap in reporting. The relevance of these findings for the interpretation of survey data is clear. Whether there is a gun reported in a home depends to a remarkable extent on which member of the household is asked the question. Hence, the method of selection of respondent(s) from within a household will affect estimates of the patterns and prevalence of gun ownership, and, potentially, the accuracy of case–control studies that use self-report information about guns in the home